Rezension von: Brecht, Martin, Sein Weg zur Reformation 1483-1521 - Wissner, Martin (Württembergisch Franken, 1983)
Martin Brecht: Martin Luther - Sein Weg zur Reformation 1483-1521. Stuttgart: Calwer Verl. 1981. 527 S.